(3GdCfhGQ GdMSfjI aj fSHI ef HSLdeGSI ef GdCTQGa GdoeMeOjIs - (3CHh GdYHGS CMeO Hf eMeO Hf CMeO Hf eMeO Hf YHO GdYRjR Hf GdMSf Hf jhSa GdMSfjs
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdCTQGa ef PQjI aGWeI HfJ eMeO Udi Gddg Ydjg hSde CeGfG dgPg GdCeI eGOGehG ehLhOjf s
(3BNQgG (B:s
(3hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde JSdjekG ddg QH GdYGdejf hdGMhd hdGbhI EdG HGddg GdYdi GdYXje s
(3Vef eLehY , JQJjHgG (B: (3ef U (B33 (3H (B- (3U(B66 (3Hs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B56 ; (3agQSJ GdNRGfI GdYGeI HGdQHGW (B- (3GdLRA (B2 - (3U (B152 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B((3O (B1351) s
Keywords: (3GdJGQjNs